2006
DOI: 10.1002/ijc.22226
|View full text |Cite
|
Sign up to set email alerts
|

Heritable and environmental components in cervical tumors

Abstract: The familial risk of 18,199 women with invasive and/or in situ cervix cancers when compared with that of 72,796 women free of cervical tumors was analyzed. The risk of cervical tumors was significantly higher for women with a mother and/or sister(s) with cervical tumors (odds ratio (OR) 5 1.79, 95% CI: 1.71-1.88) than with an affected grandmother and/or aunt(s) (OR 5 1.28, 1.22-1.35). This risk did not differ according to the family side of the affected relative. Taking the familial risk of 1.28 for second-deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…It is possible that familial aggregation of gynecological cancer play a role in causation of these cancers after immigration. [5][6][7][8][9] In summary, the risk of gynecological cancers in first-generation immigrants follows the risk of cancer in the country of origin, except for cervical cancer among Africans and endometrial cancer among North Americans and East Europeans. The risk and mortality of cervical, endometrial and ovarian cancers in first-generation immigrants remained the same in the second generation, which may indicate that risk and protective factors of these cancers, mainly behavioral factors, are preserved upon immigration and through the generations or present a role of familial aggregation in the etiology of these diseases.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that familial aggregation of gynecological cancer play a role in causation of these cancers after immigration. [5][6][7][8][9] In summary, the risk of gynecological cancers in first-generation immigrants follows the risk of cancer in the country of origin, except for cervical cancer among Africans and endometrial cancer among North Americans and East Europeans. The risk and mortality of cervical, endometrial and ovarian cancers in first-generation immigrants remained the same in the second generation, which may indicate that risk and protective factors of these cancers, mainly behavioral factors, are preserved upon immigration and through the generations or present a role of familial aggregation in the etiology of these diseases.…”
Section: Epidemiologymentioning
confidence: 99%
“…4 However, a familial aggregation for gynecological cancers has also been reported. [5][6][7][8][9] There are limited and controversial epidemiological data concerning whether immigration may cause significant changes in the risk and mortality of gynecological cancers. [10][11][12][13][14][15][16][17] For example, a persistent high cervical cancer risk was reported among North African immigrants in Israel, 15 whereas, in contrast, a study on Korean immigrants in the United States showed a decreased risk of cervical and an increased risk of endometrial cancers.…”
mentioning
confidence: 99%
“…[6][7][8][9][10] In a large Swedish study the correlations for cervical tumor diagnosis in first-degree relatives ranged from 0.13 to 0.17. 9 This study included data of biological and adoptive mothers, full, half and adoptive sisters, and the heritability estimate for cervical tumors was 27%.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Several studies observed familial aggregation for cervical cancer and risk ratios between 1.8 and 3.2 have been reported in first-degree relatives. [6][7][8][9][10] A seminal study in Scandinavian twins suggested that the familial aggregation for cervical cancer is not caused by shared genes, but should be attributed to shared environment because the concordance in monozygotic twins (MZ) (genetically identical) was not higher than the concordance in dizygotic twin (DZ) pairs (on average 50% shared genes). 11 In contrast, a Swedish twin study reported a moderate heritable effect of in situ cases.…”
Section: Introductionmentioning
confidence: 99%
“…2 There are other risk factors influencing cervical cancer development, such as number of parity, 3 oral contraceptives, 4 cigarette smoking, 5 and host genetic factors. 6 . As for host genetic factors, several genes are studied and may be responsible for cervical carcinogenesis, either in HPV persistence and disease progression.…”
Section: Introductionmentioning
confidence: 99%